ImproviNg Tic services in EnglaND: a multi-method study to explore existing healthcare service provision for children and young people with tics and Tourette syndrome - Tara Murphy; Joseph Kilgariff; Kareem Khan; Louise Thomson; Charlotte L Hall; Emma McNally; Sophie S Hall; Nikita R Rattu; Nadya James; Alexia Jeayes; Suzanne Rimmer; Madeleine Jane Groom (BMJ Mental Health, 2025)
Background Timely access to diagnostic assessment and treatment is essential to improve function and mitigate the risk of poor long-term outcomes in children and young people (CYP) with tics.Objective This study aimed to explore (i) how tic services for CYP in England are currently organised, including access to assessment and treatment and (ii) healthcare professionals’ (HCPs) experiences of assessing and treating tics.Methods Two methodologies were used to examine tic service provision. First, two freedom of information (FOI) requests were sent to Integrated Care Boards (FOI1) and service providers (FOI2) to gather data on referral and assessment processes, and treatments offered. Second, a national survey of HCPs explored their experiences and training needs when assessing and treating tics.Findings FOI responses indicated that 12 of 62 services (19.4%), primarily located in the London area, offered a full pathway for the referral, assessment and treatment of tics in CYP.The national survey sample (n=184) included psychologists, paediatricians, neurologists and mental health nurses. Most described services as poorly structured and reported a need for additional resources and training in the assessment and treatment of tics.Conclusions Inconsistent and underfunded tic service provision across England limits HCPs’ ability to support CYP with tics effectively. There is an urgent need to develop clear service pathways offering both assessment and treatment, and to equip HCPs with sufficient training and resources to provide appropriate care.Clinical implications Current tic service provision does not meet the healthcare needs of CYP in England. Without improvements, CYP are at increased risk of poorer long-term outcomes.